Ebselen has lithium‐like effects on central 5‐HT2A receptor function - Antoniadou, I; Kouskou, M; Arsiwala, T; Singh, N; Vasudevan, SR; Fowler, T; Cadirci, E; Churchill, GC; Sharp, T (Wiley, 2018)
Background and Purpose Lithium's antidepressant action may be mediated by inhibition of inositol monophosphatase (IMPase), a key enzyme in Gq‐protein coupled receptor signalling. Recently, the antioxidant agent ebselen was identified as an IMPase inhibitor. Here, we investigated both ebselen and lithium in models of the 5‐HT2A receptor, a Gq‐protein coupled receptor involved in lithium's actions. Experimental Approach 5‐HT2A receptor function was assessed in mice by measuring the behavioural (head‐twitches, ear scratches) and molecular (cortical immediate early gene [IEG] mRNA; Arc, c‐fos, Egr2) responses to 5‐HT2A receptor agonists. Ebselen and lithium were administered either acutely or repeatedly prior to assessment of 5‐HT2A receptor function. Because lithium and 5‐HT2A receptor antagonists augment the action of selective serotonin reuptake inhibitors (SSRIs), ebselen was tested for this activity by co‐administration with the SSRI citalopram in microdialysis (extracellular 5‐HT) experiments. Key Results Acute and repeated administration of ebselen inhibited behavioural and IEG responses to the 5‐HT2A receptor agonist DOI. Repeated lithium also inhibited DOI‐evoked behavioural and IEG responses. In comparison, a selective IMPase inhibitor (L‐690330) attenuated the behavioural response to DOI whereas glycogen synthase kinase inhibitor (AR‐A014418) did not. Finally, ebselen enhanced the increase in extracellular 5‐HT induced by citalopram, and also increased regional brain 5‐HT synthesis. Conclusions and Implications Our data demonstrated lithium‐mimetic effects of ebselen in different experimental models of 5‐HT2A receptor function, probably mediated by IMPase inhibition. This evidence of lithium‐like neuropharmacological effects of ebselen adds further support for the clinical testing of ebselen in mood disorders, including as an antidepressant augmenting agent.